Probability density of wave function of excited photoelectron: understanding XANES features - Sipr, O (Journal of synchrotron radiation, 2001)
Interpretation of XANES spectra suffers from a poor intuitive understanding of the relation between spectral features and structural elements of a material. An attempt to alleviate this shortcoming is made by exploring a spatial distribution of probability density of wave functions of photoelectrons excited during the photoabsorption process. One has to add incoherently squares of wave functions which describe participating photoelectron diffraction (PED) processes, weighted by normalized PED cross sections. As an example, we investigate probability density of wave functions relevant to Ag L1 and L3 XANES of Ag2O.